PERAMALAN JUMLAH PENERIMAAN SISWA BARU DI SSEKOLAH DASAR DHARMMALOKA PEKANBARU DENGAN MENGGUNAKAN METODE EXPONENTIAL SMOOTHING - Salim, Kelvin Rainey; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
To be able to make informed decisions regarding school policy, one of them is to determine the prediction of the number of students receiving on new academic school year. Prediction is one of the keys to success of decision making because the value of predictions of new students can be used as a reference to determine a decision. The Single Exponential Smoothing method is used to determine the predictions of student acceptance in the period of the next school year. Exponential Smoothing method is a fairly good forecasting method for long-term and medium-term forecasting. The main advantage of the Exponential Smoothing method is that it is seen from the ease of operation that is relatively low, there is little doubt whether better accuracy can always be achieved using (QS) Quantitative systems or deconposition methods that are intuitively interesting. Data to be processed is the number of student admissions for the period 1999/2000 to 2018/2019 and presented in the data for the academic year. The results obtained from this study are the results of analysis of a single exponential method to obtain information on predictions of new student admissions and the level of accuracy with MAPE.Keywords: prediction, forecasting, Single Exponential Smoothing, quantitatif.